Jewellery box: inspired by Balai Besar Kedah / Muhammad Saiful Hazim Mohamad Affandi - Mohamad Affandi, Muhammad Saiful Hazim (2022)
Balai Besar Kedah is a royal audience hall built within Kompleks Istana Kota Setar. The architecture is potraying the traditional Malay style, featuring influences of Siamese and British Colonial